"composición química y degradabilidad ruminal in situ de la cascara de maracuyá y cascarilla de arroz inoculadas con cepas de hongos Pleurotusostreatus y sapidus. Finca Experimental La María" Mocache, 2013. Quevedo. UTEQ. 79 p. - Florencia Toala, Victor Hugo (2013)
In the Quevedo city have large quantities of waste materials from agricultural and agro-industrial activities, as in the case of passion fruit peel and rice husks, which by its volume was interesting to perform this research. Which was carried out in the Laboratory of Nutrition and Metabolism Rumiology, Faculty of Animal Science, in the interest of measuring in situ ruminal degradability as dry matter (DM), organic matter (OM) mineral matter (MM) and protein (P), for which nine treatments with the use of two strains of fungi of the genus Pleurotus spp were established, with a time of 45 solid days fermentation being; T1: shell Passion , T2: Cascarilla Rice, T3: Mix 50 %, T4: Passion Fruit Peel + P. Ostreatus , T5: Rice Husks + P. Ostreatus, T6: Mix 50% + P. Ostreatus; T7: Passion Fruit Peel + P. Sapidus; T8: Rice Husks + P. Sapidus; T9: Mix 50% + P. Sapidus. The art of nylon bag was used to determine these variables three fistulated Brahman breed of cattle took advantage. Ruminal incubation periods were 0, 3, 6, 12, 24, 48 and 72 hours. In situ degradability, the substrate with the highest representation of the MS was rice husk without inoculum, while for the MO, the largest response the present shell with passionfruit Pleurotus ostreatus and sapidus; being rice husk with Pleurotus ostreatus who reached the highest response of MM, where passion fruit peel Pleurotus ostreatus, was the one who scored the highest percentage of protein. Keywords: agricultural waste, nylon bags, in situ degradability, rumen, factors, and Pleurotus ostreatus and Sapidus.